Skin melanocytes and fibroblasts show different changes in choline metabolism during cellular senescence. (June 2017) - Windler, Cordula; Gey, Claudia; Seeger, Karsten
Highlights: Senescent skin fibroblasts and melanocytes show distinct metabolic changes. However, in both cell types the choline metabolism is affected. These changes are distinct to malignant transformed cells. Abstract: Unmodified cells undergo only a limited number of cell divisions until they enter a state termed cellular senescence. Other triggers like cytotoxic compounds can also induce cell senescence. Since cell senescence represents a major mechanism of tumor suppression this cellular state has attracted increasing attention. Different markers like senescence-associated β-galactosidase (SAβGal), senescence-associated heterochromatic foci (SAHF) or certain metabolic changes have been identified to be characteristic for senescent cells; however, data is often limited to fibroblasts − the cardinal model system for cellular senescence. In order to investigate whether metabolic changes during senescence are cell type independent, skin fibroblasts and skin melanocytes have been examined. Expression of the senescence marker p16 could be detected in skin fibroblasts but not in melanocytes of this specific donor, rendering the senescent phenotype not fully ascertained for the melanocytes. Metabolic profiles of senescent cells and controls have been determined using NMR spectroscopy. Changes in metabolism are different for fibroblasts and melanocytes. Senescent melanocytes showed lower levels of phosphocholine whereas for fibroblasts in accordance with literature, levels of glycerophosphocholine were increased during senescence. Although no general metabolic marker for cellular senescence exists, the same metabolic pathway seems to be affected for both cell types.